Implementasi Strategi Komunikasi Pemasaran Produk Cawang AC Pro PT Gobel Dharma Nusantara di Masa Pandemi Korona - Dwi Kartikawati (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
The research focused on the implementation of marketing communication strategy on Cawang Pro Air Conditioning Product at PT Gobel Dharma Nusantara during the corona virus pandemic . Since the corona virus (covid-19) pandemic has spread to almost all corners of the world, has hit the business of goods and services. Many companies must quickly adapt to this condition and also very tight business competition in Air Conditioning products. PT Gobel Dharma Nusantara must adjust to these conditions to anticipate the product disappearing from the market, which is caused by the health crisis. The theoretical framework used in this study is the concept of marketing communication, model concept, marketing communication strategy, online media utilization and AISAS theory. This research was qualitative research with a case study method. The results showed that the implementation of the marketing communication strategy at PT. Gobel Dharma Nusantara have done 3 strategic steps. The first step is planning communication marketing including determining marketing communications objectives, setting a marketing communications budget, and determining the development of marketing communications programs. The second step is executing on marketing communications by changing the tools and elements of marketing communications digitally. The third step is evaluating. Thus, the entire implementation of marketing communications is carried out continuously so that the company continues to exist in the midst of the corona virus pandemic situation